Enantioselective α-Benzylation of Aldehydes via Photoredox Organocatalysis - Shih, Hui-Wen (2010)
The first enantioselective aldehyde α-benzylation using electron-deficient aryl and heteroaryl substrates has been accomplished. The productive merger of a chiral imidazolidinone organocatalyst and a commercially available iridium photoredox catalyst in the presence of household fluorescent light directly affords the desired homobenzylic stereogenicity in good to excellent yield and enantioselectivity. The utility of this methodology has been demonstrated via rapid access to an enantioen-riched drug target for angiogenesis suppression.